ШАХСЛАРАРО МУЛОҚОТ ВА МУОМАЛА МАДАНИЯТИНИНГ ПСИХОЛОГИК ХУСУСИЯТЛАРИ - Ибодуллаева, И. (SCIENCE and SOCIETY, 2018)
The article deals with the psychological features of interpersonal communication and culture of communication.